2023
DOI: 10.1038/s41598-023-37473-7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of linearly polarized microwaves on nanomorphology of calcium carbonate mineralization using peptides

Abstract: Microwaves are used for diverse applications such as mobile phones, ovens, and therapy devices. However, there are few reports on the effects of microwaves on diseases other than cancer, and on physiological processes. Here, we focused on CaCO3 mineralization as a model of biomineralization and attempted to elucidate the effect of microwaves on CaCO3 mineralization using peptides. We conducted AFM, ζ potential, HPLC, ICP-AES, and relative permittivity measurements. Our findings show that microwaves alter the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…A thermocouple thermometer (Card Logger MR5300, MR9302, CHINO Corp., Tokyo, Japan) was used to measure the temperature changes in Milli-Q water (1 mL) in a microtube upon MW irradiation from one direction at 10, 30, and 200 W or from two directions at 10 and 200 W. In the previous study, we already confirmed that the effect of MWs on the thermometer was negligible [26].…”
Section: Measurements Of Sample Temperaturementioning
confidence: 75%
See 4 more Smart Citations
“…A thermocouple thermometer (Card Logger MR5300, MR9302, CHINO Corp., Tokyo, Japan) was used to measure the temperature changes in Milli-Q water (1 mL) in a microtube upon MW irradiation from one direction at 10, 30, and 200 W or from two directions at 10 and 200 W. In the previous study, we already confirmed that the effect of MWs on the thermometer was negligible [26].…”
Section: Measurements Of Sample Temperaturementioning
confidence: 75%
“…We recently reported the effect of MWs generated by a semiconductor oscillator that outputted a narrow frequency band of 2450 ± 3 MHz on CaCO 3 mineralization using peptides with different net charges. Our results showed that the nanomorphology of the CaCO 3 precipitates was dependent on the MW output (10-60 W) and the ability of the peptide to induce CaCO 3 precipitation [26]. Investigating the effects of MWs on the CaCO 3 mineralization with peptides enabled the elucidation of the molecular behavior of organic and inorganic compounds.…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations